The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1161/01.cir.0000089185.80318.3f
|View full text |Cite
|
Sign up to set email alerts
|

INR Self-Management Permits Lower Anticoagulation Levels After Mechanical Heart Valve Replacement

Abstract: Background-The Early Self Controlled Anticoagulation Trial (ESCAT I) showed that anticoagulation self-management after mechanical heart valve replacement decreased complication rates by maintaining INR levels closer to the target range than International Normalized Ratio (INR) home doctor management. The therapeutic range for the INR in that study was between 2.5 and 4.5 for all positions of prosthetic valves. ESCAT II should find out whether lowering the target range for INR self-management would further redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 11 publications
3
90
1
3
Order By: Relevance
“…11,12 The German-Dutch Ross Registry is a prospective multicenter cohort study with 1742 patients. Started in February 1991, the registry includes data from 12 cardiothoracic surgery departments in the Netherlands and Germany [7][8][9][10] (see the online-only Data Supplement for a list of participating centers).…”
Section: Source Of Study Datamentioning
confidence: 99%
“…11,12 The German-Dutch Ross Registry is a prospective multicenter cohort study with 1742 patients. Started in February 1991, the registry includes data from 12 cardiothoracic surgery departments in the Netherlands and Germany [7][8][9][10] (see the online-only Data Supplement for a list of participating centers).…”
Section: Source Of Study Datamentioning
confidence: 99%
“…A secondary end point was bleeding complications. TEs and bleeding were defined in accordance with previous reports 6,27,28 and current guidelines, 26 along with a neurologic consultation to assess strokes. Bleeding within 48 h of cardiopulmonary bypass was not taken into account.…”
Section: Follow-up and Eventsmentioning
confidence: 99%
“…Because high-intensity anticoagulation is associated with high variability, lower INR goals (possibly 2 to 3) would reduce variability. Also, higher testing frequency improves the length of time spent in the target range 33,[37][38][39] and is an incentive for anticoagulation clinics or INR selfmanagement 21,27,38 as tools to improve anticoagulation effectiveness.…”
Section: Anticoagulation Effectmentioning
confidence: 99%
“…11 Each test was followed by a telephone consult from the physician directly to the patient. For selfmanagement, we assumed that patients conducted weekly INR tests and contacted a pharmacist after each test during the first month and once a month thereafter.…”
Section: Model Inputsmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] It has been found that patients who self-manage check their INR more frequently and are able to maintain a greater proportion of INRs within the therapeutic range compared with those whose therapy is monitored by a physician or in an anticoagulation clinic. [11][12][13] The results of a recent meta-analysis showed a significant reduction in thromboembolic events (odds ratio [OR] 0.45), major hemorrhagic events (OR 0.65) and all-cause mortality (OR 0.61) for those using a self-management or self-test strategy. 14 The results also showed that self-management compared with self-testing alone reduces the occurrence of thromboembolic events (OR 0.27) and death (OR 0.37).…”
mentioning
confidence: 99%